Implementation of Micro, Small and Medium Enterprises Policy during the Covid-19 Pandemic in Sidoarjo - Sukmana, Hendra; Rodiyah, Isnaini; Mursyidah, Lailul (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
MSMEs in Indonesia play a role as a trigger for economic growth in developing and developed countries. MSMEs also have a crucial function in overcoming problems in a region or region. When the economic situation slumps due to the Covid-19 Pandemic, business people must be really observant in making decisions. The Sidoarjo government has again taken steps as a form of controlling the economic sector during the pandemic. The purpose of this study is to identify the implementation of policies to strengthen micro, small and medium enterprises during the Covid-19 pandemic in Sidoarjo. The research method used is a literature review using 25 journal articles. The results of the study show there are several MSME protection schemes carried out by the government in Sidoarjo, namely as follows: First, there is financial assistance and social assistance for MSME actors affected by Covid-19, especially those who are vulnerable and classified as very poor. Second, tax incentives for MSMEs. Third, relaxation and restructuring of credit for MSMEs through the KurdaSayang program. Fourth, expansion of MSME working capital financing. Fifth, synergistic cooperation between local governments and related stakeholders as a buffer for MSME products. Sixth, training on the use of e-learning digital platforms. Meanwhile, the implementation of policies to strengthen micro, small and medium enterprises during the pandemic in Sidoarjo, can be seen from the communication, bureaucratic structure, resources and attitude of the implementers.